Pengaruh Komunikasi Krisis Kasus Overclaim Kandungan Produk Skincare terhadap Citra Elsheskin - Raysa Nahtania; Sa’diyah El Adawiyah (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Elsheskin is a local skincare brand from Yogyakarta, which is under the auspices of PT Elshe Estetika Nusantara. In October 2024, it was circulated that Elsheskin had overclaimed the content of skincare products, because the retinol content in Elsheskin's retinol rejuvenating night serum product was proven to be inconsistent with laboratory test results. This overclaim case has damaged Elsheskin's image. The purpose of this study is to measure Elsheskin's crisis communication in dealing with the case of overclaiming the content of skincare products, Elsheskin's image after conducting crisis communication and how much influence the crisis communication of the case of overclaiming the content of skincare products has on Elsheskin's image. The theory used is the crisis communication theory (Coombs, 2019) which consists of the pre-crisis stage, the crisis event stage and the post-crisis stage. This study also uses the Image theory (Boulding, 2007) which consists of knowledge, feelings, values ​​and beliefs. The method used in this study is a quantitative approach with a survey method and a simple random sampling technique by distributing paper questionnaires to 80 respondents selected according to the characteristics of the study. From the results of calculations and data processing using the SPSS 25 application, namely: a) Elsheskin has carried out crisis communication well in accordance with crisis communication theory. b) Elsheskin has succeeded in restoring its image due to the overclaim case. c) There is an influence of crisis communication in the case of overclaiming skincare product content on Elsheskin's image of 59.2%.